THE CORRELATIONAL STUDY BETWEEN READING AND LISTENING COMPREHENSION ON TOEIC : A correlational study at a vocational school in Bandung - Rd. Wawoho Nursanto, - (2009)
This research is entitled "The Correlational Study Between Reading and Listening Comprehension on TOEIC (A Correlational Study at a Vocational School in Bandung)". It was aimed to investigate the correlation between reading and listening comprehension based on students score in TOEIC This research investigated 75 participants from a vocational school in Bandung. Having correlated the data through the test, the research used Spearman Rank Correlation Coefficients to find the correlation between both skills. It was found that there was positive correlation between skills at low degree. To conclude, it seems that the following factors may affect the result. Those were the similarities and differences characteristics between skills, the teachers' competence, and the teachers' ability in selecting the appropriate method. It was also noted that participants background knowledge and teaching materials might influence their achievement.